PERAMALAN PENJUALAN MENGGUNAKAN METODE LEAST SQUARE PADA CV RAGAM JAYA - Andika Gosal (Prosiding Seminar Nasional Indonesia, 2026)
This research aims to forecast sales using the Least Square method at CV Ragam Jaya, a medium-scale enterprise engaged in the distribution of office stationery (ATK) in Surabaya. Currently, the company relies on a manual system for managing sales and inventory, leading to inefficiencies and inaccuracies in stock control. By applying the Least Square forecasting method, the company can predict future demand trends and optimize its inventory management. The study used monthly sales data from January to September 2024. Results indicate a consistent upward trend across all product categories with Mean Absolute Percentage Error (MAPE) values below 5%, demonstrating high forecasting accuracy. This method proves effective in improving sales forecasting and supports better inventory decision-making for CV Ragam Jaya.